Finding a moral compass for South Africa Where are we? Where could we go? - Vorster, JM (AOSIS, 2023)
The research question of this book reads: Can South Africans, amidst all the contemporary distrust in political leadership and moral decay, find a moral compass that could lead them to a humane society of mutual trust, respect for each other, a flourishing life and a bright future for future generations? This book presents new perspectives on the psychopathology created by colonisation, the failures of the post-1994 dispensation regarding reconciliation, transformation, justice, distorted family life, violence, unity in diversity, as well as moral leadership and agency and indifference to a future of hope. It proposes a new moral compass that can lead South Africa out of the abyss.